Isu-Isu Kontemporer Dalam Dunia Kerja - Keiza Madinatuz Az-Zahra; Seliyana Heryani; Machdum Bachtiar (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid development of the global workforce in the era of globalization and the Fourth Industrial Revolution has led to significant changes in employment systems. Technological advancements, particularly in artificial intelligence (AI), automation, and the implementation of flexible and hybrid work models, have transformed work patterns, industrial relations, and human resource management practices. At the same time, outsourcing and the increasing number of layoffs have emerged as major challenges that directly affect workers’ economic and psychological well-being. This study aims to examine contemporary issues in the world of work, including outsourcing, artificial intelligence and automation, flexible and hybrid work models, termination of employment, and compensation systems, particularly within the context of Islamic educational institutions. This research employs a descriptive qualitative method using a library research approach by analyzing various relevant primary and secondary sources. The findings indicate that changes in the world of work offer opportunities for increased efficiency and productivity, yet also pose risks such as job insecurity, reduced employment opportunities, and challenges in maintaining a balance between organizational interests and workers’ rights. Therefore, adaptive, fair, and welfare-oriented labor policies, along with equitable, transparent, and just compensation systems, are essential to create a healthy, sustainable, and humane working environment.